Potential Cost Savings of Off-Site Regional Anesthesia for Minor Orthopedic Surgical Procedures (Pain medicine, 2016)
This study is limited by the fact that each hospital has different costs for staffing as well as ambiguous billing patterns that make it difficult to correctly appreciate the value of perioperative staffing and costs for the hospital, insurance company, and the patient. Additional costs, as noted above, that were not included in this study would be also added to the potential cost savings. Therefore, our results may in fact appreciate the true difference in costs between the operating room and treatment room anesthesia. As anesthesia providers, we are involved in the perioperative care of surgical patients. We must continuously improve our perioperative care to enhance patient safety while increasing efficiency and decreasing costs. Using regional anesthesia to minimize main operating room times may be an acceptable approach to achieving cost saving measures, as well as reducing unnecessary staffing and main operating resources.
Keywords: regional anesthesia; minor orthopedic surgical procedures; potential cost